Damage assessment, fragility, and vulnerability analysis of reinforced concrete building - Radomir Folić; Miloš Čokić; Boris Folić; Zoran Brujić (Građevinar)
In addition to a concise literature review, this study presents a comparative analysis of reinforced concrete (RC) buildings through damage index (DI) analysis using different methodologies. The seismic response of a five-story RC frame system building, designed in accordance with the EN structural Eurocodes, was analysed through fragility and vulnerability assessments. The Park–Ang methodology was used in the analysis for determining DI and its parameters. Nonlinear static analysis (NSA) and nonlinear dynamic analyses (NDA) were performed, and the fragility and vulnerability curves were constructed using the obtained results and processed through statistical analysis. The results were calculated using four different DI models: the DIPA model using both the NSA and NDA results (M1), modified DIPA model using both the NSA and NDA results (M2), DIPA model using the NSA results (M3), and modified DIPA model using the NSA results (M4).